The Predictive Power of Limited Information in Preliminary Analytical Review: An Empirical Study - Kinney, William R. (Journal of Accounting Research, 1979)
William R. Kinney, Jr., The Predictive Power of Limited Information in Preliminary Analytical Review: An Empirical Study, Journal of Accounting Research, Vol. 17, Studies on Auditing-Selections from the "Research Opportunities in Auditing" Program (1979), pp. 148-165